Pencatatan Perkawinan Beda Agama Menurut Hukum Positif Indonesia - Pratama, Muhammad Fachrisyah; Hadiati, Mia (Syntax Literate, 2023)
Marriage registration plays a central role in the legal system and government administration to record and protect individual rights while managing marital status within a society. This research delves into the significance and impact of marriage registration in the context of civil law and public administration. Through the analysis of marriage regulations, registration procedures, and their legal implications, this study identifies the role of marriage registration in acknowledging the rights and obligations of spouses, as well as protecting the interests of children. The research also explores the evolution of marriage registration in response to social and technological changes, along with its implications for accessibility and data security. The research findings highlight the importance of efficiency and transparency in the marriage registration process to ensure the protection of individual rights and provide a strong foundation for law enforcement. Further understanding of the role of marriage registration can serve as a basis for improving marriage administration systems and supporting policy reforms that promote justice and legal security.